PEMERIKSAAN HBSAG PADA MASYARAKAT RT. 06 RW. 02 KELURAHAN SUKAJAYA PALEMBANG GUNA MENINGKATKAN KUALITAS KESEHATAN - Hotman Sinaga; Maria Nuraeni (Universitas katolik Musi Charitas, 2017)
Hepatitis B still becomes a big health problem in many countries including Indonesia. Transmission of the disease by the hepatitis B virus easily occurs. The virus can be identified in most of the body fluids such as saliva, semen, breast milk and serous cavity fluid. Every person has the risk of contracting Hepatitis B. The people do not realize that they are infected by the Hepatitis B virus, because their health is still in good condition and can transmit it to others. And for the patients, their condition can be worse because it can develop into chronic infection that can cause to cirrhosis and liver cancer. The purpose of the examination of the HBsAg for the people in Rt.06 of Sukajaya is to know how their health status concerning Hepatitis B infection. The method of this activity is carried out in a survey to determine the number of people as well as of their knowledge about Hepatitis B, and then will be held the examination of the HBsAg.The result of the examination of 44 people are known to all negative, but a survey of 185 people as many as 174 people are less aware of the danger of Hepatitis B virus. Therefore, it urges to give valuable information about the disease, and giving vaccination for people who do not have immunity power to exist Hepatitis B virus is highly recommended.